METODE PEMBELAJARAN ALA RASULULLAH SAW (KAJIAN TENTANG METODE PENGAJARAN RASULULLAH SAW DITINJAU DARI HADIST) - Fajar Tresna Utama; Aidillah Suja; Cahya Edi Setyawan (STAI Masjid Syuhada Yogyakarta, 2021)
There is a term in Arabic “الطريقة أهمّ من المادة” which means that the method is more important than the material to be conveyed. From this expression, it can be understood that a learning method occupies an important role in the learning process. Choosing the right learning method will make it easier for teachers to achieve learning goals effectively and efficiently, and the Prophet Muhammad himself has provided examples in applying the right methods in his learning to his people, so that learning objectives can be achieved effectively and efficiently and proven by the development of Islam until it reaches us today.